Performance of MIMO radar using two-way music - De Silva, Pasan (2014)
Multiple Input Multiple Output (MIMO) concept have been a prevalent technology in the wireless communication system (IEEE 802.11n and 4G), as it helps to increase transmit power and data throughput by array gain and diversity gain, while reducing multipath fading. In recent years, the concept of MIMO technology has been exploited for outdoor RADAR system for direction finding of targets besides using the conventional mono-static and bi-static radar system. Direction finding subspace algorithms such as MUSIC, ESPRIT have been often used to estimate the angle of arrival (AOA) of signal path that has been transmitted from the single element transmitters. In this paper, we explore using the MUSIC algorithm for direction finding of the target in the space for RADAR system equipped with antenna array at both transmitter and receiver. This algorithm is known as Two-way MUSIC for MIMO RADAR system. We will assess the performance of the Two-way MUSIC algorithm for MIMO RADAR such as the advantages and limitations in terms of maximum number of target elements that can be detected for given number of transmitters and receivers. We will also explore the optimum performance of the system for different practical scenarios.